Hamiltonian flow of Yang-Mills theory in Coulomb gauge - Reinhardt, Hugo; Pawlowski, Jan M. (Arxiv, 2010)
A new functional renormalization group equation for Hamiltonian Yang-Mills theory in Coulomb gauge is presented and solved for the static gluon and ghost propagators under the assumption of ghost dominance. The results are compared to those obtained in the variational approach.